The Natural Cooperatives in The Muslim World: Traditional Entrepreneurial Communities - Javaid, Omar (Invest Journal of Sharia & Economic Law, 2024)
This study investigates traditional Muslim entrepreneurial communities by comparing them with modern Western cooperative models. Unlike Western cooperatives, which emerged to counter market-induced social disintegration, Muslim communities have sustained themselves through kinship networks, shared values, and voluntary socioeconomic justice. Muslim cooperatives are more organically rooted in local traditions than Western cooperatives. The key characteristics of these communities include family-business integration, mutual financial support, job creation, and community well-being, aligning with cooperative aims. Despite their benefits, contemporary research on these communities remains limited and often outdated. This contrasts with extensive studies on ethnic entrepreneurship in non-Muslim contexts. This study advocates for more research to understand how Muslim entrepreneurial communities maintain social integration, distributive justice, and Islamic values. It proposes research questions on community organization, economic contributions, welfare mechanisms, and modernization impacts to inform policies and development. The study aims to enhance the understanding of Islamic socioeconomic models by examining communities' resilience and adaptability.